The Effect of the Augmented Reality Applications in Science Class on Students' Cognitive and Affective Learning - Fatih Serdar Yildirim (Journal of Education in Science, Environment and Health)
This study aims to determine how effective science teaching with augmented reality-based teaching material (science cards) is compared to the science curriculum prescribed methods on students' academic achievement and their views on augmented reality application. As a study group, 63 students who were studying in a 7th grade in a secondary school in Antalya in the 2019-2020 academic years were selected. Mixed research design was used in the research. In the quantitative side of the research, the control group and the experimental group who are taught using the augmented reality (science cards) were compared in terms of achievement. In the qualitative side on the other hand, interview and observation data were used. The results of the research have shown that while Augmented Reality (AR) applications increase students' achievement, contribute to the meaningful learning of abstract subjects, AR applications also increase the students' interest and motivation towards science lesson.